2017
DOI: 10.2305/iucn.ch.2017.parks-23-1k-zi.en
|View full text |Cite
|
Sign up to set email alerts
|

Using a participatory assessment of ecosystem services in the Dinaric Arc of Europe to support protected area management

Abstract: Economic and non-economic benefits of protected areas were assessed in 58 national parks in the Dinaric Arc of Europe, involving over a thousand local people and identifying major economic benefits from tourism, rural development and water. The study used the Protected Area Benefits Assessment Tool in stakeholder workshops in all the parks studied. The results are being applied to improve protected area management and enhance collaboration with local stakeholders. The Dinaric Arc includes parts of eight countr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 6 publications
0
5
0
2
Order By: Relevance
“…The 49 studies selected to be included in this review where from 17 European countries (Table S1, Supplementary material). The largest studies were 6 national reports ( Ivanić et al, 2017 ) using the PA-BAT tool ( Dudley and Stolton, 2009 ) assessing benefits in several national parks across different East European countries. The number of studies has increased in the past decade, as shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 49 studies selected to be included in this review where from 17 European countries (Table S1, Supplementary material). The largest studies were 6 national reports ( Ivanić et al, 2017 ) using the PA-BAT tool ( Dudley and Stolton, 2009 ) assessing benefits in several national parks across different East European countries. The number of studies has increased in the past decade, as shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…A number of studies focus on the benefits of conservation on these broad categories (e.g. Ivanić et al, 2017 ). However, the designation of PAs is linked both with negative and positive aspects of these impacts for users ( Jones et al, 2017 , 2018 ; Oldekop et al, 2015 ) that need to be taken into consideration both before and after the PA designation.…”
Section: Social Impacts Of Protected Areasmentioning
confidence: 99%
“…To establish a supportive attitude towards PAs among the range of stakeholders, it is vital to communicate effectively and achieve a common understanding of PA values and benefits, hence laying a robust ground for management and policy development (Ivanić et al 2017). In this regard, the importance of the perception of people living in protected areas has been particularly highlighted (Pelegrina-López et al 2018;Hirschnitz-Garbers and Stoll-Kleemann 2011).…”
Section: The Importance Of Participatory Planning In Protected Area Managementmentioning
confidence: 99%
“…Процена екосистемских услуга доприноси и реализацији глобалних циљева одрживог развоја до 2030. године, а нарочито циља број 15, подциљ 15.4. према којем је потребно очувати екосистеме ради пружања користи од суштинског значаја за одрживи развој (UN, 2015). Нарочито је важно укључивање различитих интересних група у доношење одлука у управљање природним добрима (Ivanić et al, 2017;Dobričić & Josimović, 2018), као и укључивање резултата вредновања екосистемских услуга у друге секторске области (Stojkov & Dobričić, 2012;Dobričić et al, 2017;Dobričić, 2012). Тако нпр, према Lam & Conway (2018) политика планирања коришћења земљишта кроз израду планских докумената помаже власти да планира, регулише и различитим политикама и мерама усмерава одрживи просторни развој тог подручја, али и доприноси заштити и унапређењу екосистемских услуга у овим подручјима.…”
unclassified
“…PA-BAT метод је осмишљен од стране Dudley & Stolton (2009) и до сада je примењен на заштићеним подручјима у седам земаља Динарског лука (Ivanić et al, 2017), и то: Словенији, Хрватској, Босни и Херцеговини, Црној Гори, Северној Македонији, Албанији и Србији. Поред наведених земаља југоисточне Европе PA-BAT метод је примењен и у другим земљама света, као што су Колумбија, Турска, Мјанмар, САД и Етиопија (Ivanić et al, 2020).…”
unclassified